Factors Related To Outcome of Traumatic Brain Injury Patients at M Djamil Padang Hospital - Nora Fitri; Syarif Indra; Hendra Permana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Traumatic brain injury is still a major threat because it can cause global morbidity and mortality. Many factors can affect the outcome of a traumatic brain injury. Some conditions that can exacerbate traumatic brain injury include GCS conditions, blood pressure variability, and pupillary reflexes.Methods: The research was conducted in M. Djamil Padang Hospital from October 2020 to March 2021. The study design was a cross-sectional study in traumatic brain injury patients with ≤ 48 hours of onset and the aged between 18-60 years. The subjects in this study consisted of 66 subjects. At 6 weeks after onset, a GOS assessment was performed to assess patient outcomes. Statistical analysis was performed computerized with SPSS 22.0. P-value <0.05 was considered statistically significant. Results: Most of the patients were male (71.2%) with an average age of 36.41 ± 14,275 years, and the most common injury mechanism was traffic accidents (95.5%). There was a significant relationship between onset of incidence, hypotension, pupillary reflexes, and Rotterdam score with the outcome of traumatic brain injury patients (p<0.05) and there was no significant relationship between age, gender, and mechanism of injury with the outcome patients with traumatic brain injury. Conclution: The onset of events, hypotension, pupillary reflexes, and Rotterdam scores significantly affect the outcome patients of traumatic brain injury.